Body as an instrument of protest: feminist narratives in dance performances - Bugayets, Nataliya; Ostroverkh, Yelizaveta (Professional Art Education, 2025)
Object. The article analyzes feminist dance performances in which corporeality becomes an instrument of political protest and social reflection. The study focuses on how the body, as an expressive and communicative medium, challenges dominant discourses about gender and power. Corporeality in feminist performance transforms the stage into a space of dialogue, resistance, and the rethinking of identity. Through movement and choreographic expression, dancers articulate social critique and reveal ways to challenge patriarchal norms through artistic means. Purpose of the study. The study examines the phenomenon of feminist dance performances where corporeality functions as a tool of political protest and social criticism. The main goal is to identify how the body acts simultaneously as a means and a message in the construction of feminist discourse. Methods & methodology. The research employs an interdisciplinary approach combining aesthetic, cultural, feminist, and art-historical analysis. Comparative and hermeneutic methods are used to interpret the works of Martha Graham, Pina Bausch, Simone Forti, Anna Halprin, and other choreographers. The methodological foundation includes concepts of performativity (J. Butler), body politics (S. Baines), and intersectional feminist analysis. Results. The findings show that corporeality in feminist performance serves as a key instrument for articulating and critiquing patriarchal norms. The body functions as an active subject conveying emotional, traumatic, and collective experience. The main features of such performances include the deconstruction of gender stereotypes, emancipated movement, viewer involvement, and embodiment as a form of representing memory and trauma. The study also clarifies the impact of these practices on contemporary art and broader sociocultural processes, including the Ukrainian context. Conclusions. Corporeality in feminist performance carries aesthetic, social, and political dimensions, becoming a medium of protest and self-exploration. Feminist practices expand the boundaries of choreography, affirming the body as an autonomous subject of cultural communication. Further research into these phenomena remains important in the context of ongoing social transformations.